Application of Optical Fiber in Engineering - Wadi Harun, Sulaiman (IntechOpen, 2021)
Application of Optical Fiber in Engineering chronicles the recent progress in the research and development of optical fiber technology and examines present and future opportunities by presenting the latest advances on key topics such as birefringence and polarization mode dispersion characteristics, quantum communication, polymer optical fiber grating, optical fiber sensing devices and the Raman fiber laser. All the contributing authors are experts in the field, and this book contains their latest research. This book will provide an invaluable source for researchers, engineers, and advanced students in the field of optical fibers, photonics, optoelectronics, fiber lasers, and sensors.